Theophany: the neoplatonic philosophy of Dionysius the Areopagite - Perl, Eric David (SUNY series in ancient Greek philosophy, 2007)
Beyond being and intelligibility -- Being as theophany -- Goodness, beauty, and love -- The problem of evil -- The hierarchy of being -- The continuum of cognition -- Symbolism